Shipping conferences and antitrust exemption in North America from a Canadian perspective: New life in an old debate - Jermyn, Glen (Shipping Law Unit, 2023)
Transport Canada defines shipping conferences (herein "conferences") as follows: "Ocean liner shipping companies [which] offer regularly scheduled ocean transportation services, as opposed to irregular or non-liner services, primarily consisting of the carriage of containerized cargo rather than bulk commodities. A conference is an association of liner companies operating under an agreement to provide service on common trade routes and which collectively agree on rates and terms of service."